THE INFLUENCE OF SOME FACTORS ON MILK CONTENTS OF SOMATIC CELLS IN HOLSTEIN COWS - Shana S. A. Jaaf (Mesopotamia Journal of Agriculture)
70 Holstein cows were randomly chosen from the herd at the Nasr Dairy Cattle Station, United Company for Animal Resources Ltd ., Al-Soueira ( 50 Km south of Baghdad ) and over period from December, 2003. The aim of this investigation was to study the effects of some factors on somatic cell count (SCC) in milk. The overall mean of the SCC in milk was (1584.314 x 103 cell/ml). Cows which produced milk less than 3000 kg/season, showed higher level of SCC (2047.461 x103) cell/ml. Also the infected cows had higher SCC compared with healthy cows and the difference was not significant in this study. The regression coefficient of SCC on age at first calving (A.F.C.) was significant (P <0.01) (9x103 cell / month). The correlation coefficient between lactation period, milk production and SCC were negative P < 0.01 and were (-0.16, -0.09) respectively.